How Significant Are Externalities for Development? - Stewart, F; Ghani, E (1991)
This paper provides an assessment of the magnitude and policy significance of externalities in developing countries. Much past analysis has focused on static externalities. The analytic survey of concepts and evidence, however, suggests that dynamic externalities are of major significance--in particular the nonmarket transmission of technological innovation and the cumulative interaction of learning economies, scale economies, innovation and market growth. Examples of the history of the semiconductor industry in the United States and agroindustrial development in the Punjab illustrate. Policy implications include protection and subsidization of industries particularly subject to this process.